APPLICATION OF JIGSAW-TYPE COOPERATIVE LEARNING MODEL TO IMPROVE PKN LEARNING OUTCOMES IN CLASS V AT SD NEGERI 79 LUBUKLINGGAU - Cinta Sabrin (CV Grasta Glory, 2025)
This study was conducted to determine the effectiveness of the application of the Jigsaw type cooperative learning model in improving the learning outcomes of Civic Education (PKn) students in grade V of SD Negeri 79 Lubuklinggau. This study is experimental research using the One Group Pretest and Post-test Design method. The number of class V students was 18 people who were the research sample. The instrument used was a multiple-choice test of 20 questions given before and after the application of the model. Based on the results of data analysis, a significant increase in student learning outcomes was obtained after the implementation of the Jigsaw learning model. Most students have achieved the Minimum Completeness Criteria (KKM) set by the school. The Jigsaw learning model can increase students' activeness, sense of responsibility, and the ability of cooperative skills in understanding the material. This study proposes the use of the Jigsaw learning model as an alternative to active learning in PKn subjects in elementary schools. Thus, the Jigsaw model has been shown to be effective in improving learning outcomes and student participation in PKn learning in elementary schools.